2002
DOI: 10.1016/s0022-1031(02)00510-3
|View full text |Cite
|
Sign up to set email alerts
|

Inferring speakers’ physical attributes from their voices

Abstract: Two experiments examined listenersÕ ability to make accurate inferences about speakers from the nonlinguistic content of their speech. In Experiment I, na€ ı ıve listeners heard male and female speakers articulating two test sentences, and tried to select which of a pair of photographs depicted the speaker. On average they selected the correct photo 76.5% of the time. All performed at a level that was reliably better than chance. In Experiment II, judges heard the test sentences and estimated the speakersÕ age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
121
1
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(132 citation statements)
references
References 24 publications
8
121
1
2
Order By: Relevance
“…While our data show that WHR is related to voice attractiveness in females, there was no evidence for an association between BMI and voice attractiveness for either sex. Some findings show that height and weight can be estimated from voice samples (Krauss et al, 2002;Lass & Colt, 1980;Lass & Davis, 1976). But when it comes to ratings of voice attractiveness, our results show that height and weight, as scaled by BMI, are not related.…”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…While our data show that WHR is related to voice attractiveness in females, there was no evidence for an association between BMI and voice attractiveness for either sex. Some findings show that height and weight can be estimated from voice samples (Krauss et al, 2002;Lass & Colt, 1980;Lass & Davis, 1976). But when it comes to ratings of voice attractiveness, our results show that height and weight, as scaled by BMI, are not related.…”
Section: Discussioncontrasting
confidence: 53%
“…Listeners exposed to voice samples are also capable of estimating the age, height, and weight of speakers with the same degree of accuracy achieved by examining photographs (Krauss, Freyberg, & Morsella, 2002;Lass & Colt, 1980;Lass & Davis, 1976). Independent raters are also capable of matching a speaker's voice with the person's photograph over 75% of the time (Krauss et al, 2002). Hughes, Harrison, and Gallup (2002) found that individuals with symmetrical morphological traits were rated as having more attractive voices, and as deviations from bilateral symmetry increased, ratings of voice attractiveness decreased.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…And if the voice does not agree with the looks, what affects the perceiver more, picture or sound? Differences in estimations made from voices and pictures were examined by Krauss et al (2002). They carried out two experiments in which they compared age estimation from photographs and from voices.…”
Section: General Effectsmentioning
confidence: 99%
“…A recent review of previous studies on human listener judgments of speaker age may be found in [3]. Of the studies reported which used numerical age estimation and [5] 7.1 Limited age-range Amilon et al, 2009 [6] 9.7 Moyse et al, 2014 [7] 10.8…”
Section: Introductionmentioning
confidence: 99%